In Situ Reversible Ionic Control for Nonvolatile Magnetic Phases in a Donor/Acceptor Metal‐Organic Framework. (29th December 2016) - Taniguchi, Kouji; Narushima, Keisuke; Sagayama, Hajime; Kosaka, Wataru; Shito, Nanami; Miyasaka, Hitoshi
Abstract : Reversible magnetic control by electrical means, which is highly desired from the viewpoint of fundamentals and technological applications such as data storage devices, has been a challenging topic. In this study, the authors demonstrate in situ magnetic phase switching between the ferrimagnetic and paramagnetic states of an electron‐donor/‐acceptor metal‐organic framework (D/A‐MOF) using band‐filling control mediated by the Li + ‐ion migration that accompanies redox reactions, i.e., "magneto‐ionic control". By taking advantage of the rechargeability of lithium‐ion battery systems, in which Li + ‐ions and electrons are simultaneously inserted into/extracted from a cathode material, the reversible control of nonvolatile magnetic phases in a D/A‐MOF has been achieved. This result demonstrates that the combination of a redox‐active MOF with porous flexibility and ion‐migration capability enables the creation of new pathways toward magneto‐electric coupling devices in the field of ionics. Abstract : In situ reversible magnetic phase switching between nonvolatile paramagnetic and ferrimagnetic states has been demonstrated in an electron‐donor/‐acceptor metal‐organic framework by a lithium ion battery (LIB) system . Selective electron‐filling control of acceptor sites based on the LIB voltage has been achieved by the Li + ‐ion migration accompanying redox reaction; magneto‐ionic control. On/off switching of exchange interaction paths has been realized.